A convenient synthetic approach to 5-(het)arylhydrazine substituted 1,2,4-triazines - A. P. Krinochkin; M. R. Guda; A. Rammohan; D. S. Kopchuk; G. V. Zyryanov; V. L. Rusinov; O. N. Chupakhin (Chimica Techno Acta)
A convenient synthesis of 1,2,4-triazines bearing the moieties of (hetero)arylhydrazines at the position of C5 of the 1,2,4-triazine core is reported.